Organização da Atenção Primária à Saúde para o enfrentamento da pandemia de Covid-19 no estado de São Paulo - Camargo, Ana Júlia (2024)
The objective of this study was to evaluate Primary Health Care services in the fight against Covid-19 in the State of São Paulo. This is an analytical cross-sectional study conducted with 261 PHC managers from the 17 Regional Health Departments of the state of São Paulo. For data collection, a questionnaire was built based on the Protocol for the Clinical Management of Coronavirus (Covid-19) in the Primary Health Care of the Ministry of Health and it was sent by email to the health secretariats of the municipalities of São Paulo. The data were analyzed considering the population size of the municipalities, Human Development Index and coverage of the Family Health Team and Primary Care Team . For this purpose, the Poisson regression model with random effect was used, the analyses were performed using the SAS 9.4 software and the graphs using the R4.1.2, 5% was adopted as the level of significance. The research was approved by the Research Ethics Committee of the Federal University of São Carlos. A total of 261 managers participated in the study, of which 215 (82.3%) were female, 37 (14.1%), 35 (13.4%), 32 (12.2%) and 28 (10.7%) of the interviewees, respectively, from DRS XV- São José do Rio Preto, IX-Marília, I-Grande São Paulo and VI-Bauru. Regarding the training and role of managers, it is noteworthy that 192 (73.6%) had training in the area of Health Sciences and 60 (23%) were health secretaries. When analyzing the participation of managers by population size of the municipalities, 53 (20.3%) belonged to municipalities of population size 4, that is, with a population of 20001 to 50000 inhabitants;211 (80.8%) belonged to municipalities with high human development index, 229 (87.7%) came from municipalities with family health team coverage below 25%, and 139 (53.3%) from municipalities with family health team coverage above 75%. Among the results, it is highlighted that the use of information technologies for telecare in pre-clinical care, diagnoses, case follow-up and consultations were 25% more prevalent in municipalities of size 1 or 2, when compared to municipalities of size 3 or 4 and 36% more prevalent in municipalities of size 1 or 2, when compared to municipalities of size 5, 6 or 7; the previous assessment by primary care team of Covid-19 cases reported in the health care networks was 32% more prevalent in municipalities with medium human development index compared to municipalities with very high human development index. On the other hand, the follow-up of users with flu-like syndrome, considered to be in the risk group for the development of the severe form of Covid-19, every 24 hours and via telephone, was 14% and 89% more prevalent in municipalities with medium human development index, respectively, than in municipalities with high and very high human development index, and 66% more prevalent in municipalities with high human development index compared to those with very high human development index. Regarding the use of technologies for telecare in pre-clinical care, diagnoses, case follow-up and consultations, it was 31% more prevalent in municipalities with primary care team coverage of less than 25% when compared to municipalities with primary care team coverage equal to 75% or more and 36% more prevalent in municipalities with primary care team coverage between 50% and 74.99% than in municipalities with primary care team coverage equal to or greater than 75%, being 24% more prevalent in municipalities with family health team coverage between 25% and 49.99% than in municipalities with coverage equal to or greater than 75%. It is concluded that the 17 regional health departments of the State of São Paulo reorganized primary health care care to cope with the Covid-19 pandemic; however, they presented similarities and differences, depending on the human development index of the municipality, size and type of service offered by this level of care.